On the Benefits of Being Alone: Scheduling Changes, Intensity of Competition and Dynamic Airline Pricing - Yannis Kerkemezos; Bas Karreman (Tinbergen Institute, 2020)
We empirically test the hypothesis that the discounts offered by firms to consumers who purchase tickets in advance increase with the intensity of competition. We develop a new measure of competition for which we use the proximity (in departure time) of a given flight to its competitors to infer the intensity of competition and estimate the impact of competition on advance purchase discounts (APDs) and the dynamic pricing of airlines by exploiting plausibly exogenous changes in the flight schedules of airlines that occur during the booking period. We find strong support for the theoretical prediction that APDs are larger when the intensity of competition is higher using a sample of airline fare quotes. Our results also suggest that airline price dispersion increases with the intensity of competition.
Keywords: D43; D22; L1; L9; 330; Dynamic pricing; advance purchase discounts; price discrimination; oligopoly; airlines